Kredibilitas Influencer dalam Membentuk Kepercayaan Konsumen terhadap Brand - Rifqi Adrianto (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Advertising and promotion campaigns often involve influencers to deliver messages through the media to increase consumer trust in the brand. In addition, influencers have a level of credibility which has an impact on the level of trust in the brand. Zilingo is one of the fashion e-commerce brands on the online platform, which also takes advantage of influencers' credibility in their advertising campaign strategy. However, in entering the eMarket Platform, Zilingo as a new E-commerce platform is required to be able to build brand trust in order to compete with e-commerce brands that have previously existed as market leaders. Establishing trust in a brand is very important because Brand Trust is the main consideration for consumers to buy products. The research has several variables, namely Trustworthiness, Expertise, Similarity, Attractiveness as the independent variable and Brand Trust as the dependent variable. This research uses a quantitative approach and a positivist paradigm based on observations of social realities that occur. The research population is Zilingo consumers. The data collection technique is done by using non probability sampling. Based on the calculation of the sample formula, it is known that the number of samples in this study was 100 respondents. The results showed that Trustworthiness, Expertise, Similarity, Attractiveness had a significant positive effect on Brand Trust. Abstrak. Kampanye periklanan dan promosi seringkali melibatkan influencer untuk mengantarkan pesan melalui media guna meningkatkan kepercayaan konsumen terhadap brand. Selain itu, Influencer memiliki tingkat kredibilitas yang berdampak pada tingkat kepercayaan terhadap brand. Zilingo merupakan salah satu fashion e-comerce brand pada Platform online, yang juga memanfaatkan kredibilitas influencer dalam strategi kampanye iklannya. Namun, dalam memasuki eMarket Platform, Zilingo sebagai new E-comerce dituntut mampu membangun kepercayaan brand agar dapat bersaing dengan e-comerce brand yang telah lebih dahulu ada sebagai market leader. Membentuk kepercayaan terhadap brand merupakan hal yang sangat penting karena Brand Trust menjadi pertimbangan utama konsumen untuk membeli produk. Dalam penelitian memiliki beberapa Variable yaitu Trustworthiness, Expertise, Similarity, Attractiveness sebagai Variable independent dan Brand Trust sebagai Variable dependent. Dalam penelitian ini digunakan pendekatan kuantitatif dan paradigma positivism berdasarkan pengamatan terhadap realitas sosial yang terjadi. Populasi penelitian yaitu konsumen Zilingo. Teknik pengumpulan data dilakukan dengan non probability sampling. Berdasarkan perhitungan rumus sampel diketahui bahwa jumlah sampel penelitian ini adalah 100 responden. Hasil penelitian menunjukkan bahwa Trustworthiness, Expertise, Similarity, Attractiveness memiliki pengaruh positif yang signifikan terhadap Brand Trust.